Rare Case Report of Mature Mesenteric Teratoma in a 35-Year-Old Female - Shrestha, Man Mohan Bir; Sharma, Umesh Kumar; Thapaliya, Suraj; Limbu, Jayanti (Medical Journal of Eastern Nepal, 2022)
Teratomas are germ cell tumors that usually occur in the gonads, and present in early age group. Mesenteric teratoma is rare. Patients with mesenteric teratoma may remain asymptomatic or may present with compressive symptoms. Teratomas contain derivatives of all three germ layers, hence may contain diverse tissues. Computed tomography (CT) scan is ideal to establish the diagnosis of mesenteric teratoma, and reveal fluid, fat, calcifications, fat-fluid level. This is a case of 35-year-old female, who presented with upper abdominal pain for 2 months. She underwent Computed Tomography (CT) scan which revealed large well circumscribed mass in left upper abdomen, containing fluid, fat, and globular calcifications. Size of the lesion was: craniocaudal dimension= 12 centimeter, transverse diameter = 10 centimeter, anteroposterior diameter = 10 centimeter. Patient was managed by complete surgical resection. Histopathological examination confirmed the diagnosis of mature teratoma of mesentery.